Field-Observed Angles of Repose for Stored Grain in the United States - Bhadra, Rumela; Casada, Mark E.; Thompson, Sidney A.; Boac, Josephine M.; Maghirang, Ronaldo G. (My University, 2017)
Bulk grain angle of repose (AoR) is a key parameter for inventorying grain, predicting flow characteristics, and designing bins and grain handling systems. The AoR is defined for two cases, piling (dynamic) or emptying (static), and usually varies with grain type. The objective of this study was to measure piling angles of repose for corn, sorghum, barley, soybeans, oats, and hard red winter (HRW) wheat in steel and concrete bins in the United States. Angles were measured in 182 bins and 7 outdoor piles. The piling AoR for corn ranged from 15.7° to 30.2° (median of 20.4° and standard deviation of 3.8°). Sorghum, barley, soybeans, oats, and HRW wheat also exhibited a range of AoR with median values of 24.6°, 21.0°, 23.9°, 25.7°, and 22.2°, respectively. Angles of repose measured for the seven outdoor piles were within the ranges measured for the grain bins. No significant correlation was observed between AoR and moisture content within the narrow range of observed moisture contents, unlike previous literature based on laboratory measurement of grain samples with wider ranges of moisture content. Overall, the average measured piling AoR were lower than typical values cited in MWPS-29, but higher than some laboratory measurements.
Citation: Bhadra et al. (2016). Field-Observed Angles of Repose for Stored Grain in the United States. Applied Engineering in Agriculture, 33(1), 131-137. Doi:10.13031/aea.11894
Keywords: Angle Of Repose; Moisture; Grain Bins; Corn; Wheat; Sorghum